2014
DOI: 10.1016/j.ijhydene.2014.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Improving gasoline direct injection (GDI) engine efficiency and emissions with hydrogen from exhaust gas fuel reforming

Abstract: Graphical Abstract AbstractExhaust gas fuel reforming has been identified as a thermochemical energy recovery technology with potential to improve gasoline engine efficiency, and thereby reduce CO2 in addition to other gaseous and particulate matter (PM) emissions. The principle relies on achieving energy recovery from the hot exhaust stream by endothermic catalytic reforming of gasoline and a fraction of the engine exhaust gas. The hydrogen-rich reformate has higher enthalpy than the gasoline fed to the refor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…Finally, Fennell et al [36,37] successfully demonstrated the practical feasibility of the concept in a modern, full scale prototype gasoline direct injection (GDI) engine coupled with a reformer. The substantial amount of work reviewed here shows that on-board reforming is a feasible strategy to increase overall system efficiency, which is fuel flexible and crosscompatible between many combustion strategies.…”
Section: Homogeneous Charge Compression Ignition (Hcci) Partially Prmentioning
confidence: 99%
“…Finally, Fennell et al [36,37] successfully demonstrated the practical feasibility of the concept in a modern, full scale prototype gasoline direct injection (GDI) engine coupled with a reformer. The substantial amount of work reviewed here shows that on-board reforming is a feasible strategy to increase overall system efficiency, which is fuel flexible and crosscompatible between many combustion strategies.…”
Section: Homogeneous Charge Compression Ignition (Hcci) Partially Prmentioning
confidence: 99%
“…Emphasis was placed on comparing REGR to the baseline gasoline engine, and also to conventional EGR. The results demonstrate the potential of REGR to simultaneously increase thermal efficiency, reduce gaseous emissions, and decrease PM formation [34].…”
Section: Biofuels -Status and Perspectivementioning
confidence: 68%
“…In terms of emissions, EGR is reported to improve regulated emissions except for THC, mainly due to the high EGR heat capacity that reduces the HC oxidation rate and may cause engine to misfire when high EGR rates are used [29,31]. The effect of EGR on particle emissions in GDI engines has been also reported.…”
Section: Introductionmentioning
confidence: 99%